Development of a Stirred Yogurt Enriched with Carob Syrup and Powder - BRAHMI-CHENDOUH, Nabila (Biopolymer Applications Journal, 2026)
<audio class="audio-for-speech"></audio> Translator <audio class="audio-for-speech"></audio> Translator Yogurt is a widely consumed dairy product appreciated for its taste, nutritional quality, and versatility. Carob (Ceratonia siliqua L.), a naturally gluten-free leguminous fruit, is rich in sugars, dietary fiber, and antioxidant compounds. Its consumption is associated with several health benefits, including weight management, relief from digestive disorders and diarrhea, and potential protective effects in individuals with hypertension or kidney stones. Recognized as safe by the U.S. Food and Drug Administration (FDA), carob represents a valuable functional ingredient. This study aimed to evaluate the incorporation of carob powder and syrup into yogurt to develop a functional dairy product with improved nutritional and physicochemical properties. Three formulations were prepared: a control E (without carob), E1 (1% powder, 15% syrup), and E2 (3% powder, 9% syrup). E1 showed the highest acidity, °Brix, and viscosity, reflecting the strong structuring effect of combined carob powder and syrup. E2 exhibited intermediate values, while the control had the lowest measurements. The results demonstrate that carob addition enhances yogurt’s nutritional profile, texture, and overall quality. The strategic combination of powder and syrup provides both functional and technological benefits, creating a marketable product that aligns with consumer preferences and health-promoting properties